2008
DOI: 10.1063/1.2936087
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of nanoscale conducting paths and their control in nickel oxide (NiO) thin films

Abstract: The behavior of unipolar resistance switching in NiO thin film was investigated. The switching current and the switching voltage alone did not follow statistical distribution. Instead, it was observed that product of switching current and switching voltage; namely, switching power follows Poisson’s distribution. An electrical manipulation—pulse train, for example—was suggested in order to minimize switching failure based on the above Poisson’s distribution behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…I T has been demonstrated that the resistive switching in NiO thin films is controlled by electrical power and subject to Poisson distribution when electrical power consumed during switching is properly quantified [1]. The electrical power consumption values were quantified by grouping them with proper range, so that the data may be fitted to Poisson distribution with the normalized electrical power values of natural number m, as reported in [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I T has been demonstrated that the resistive switching in NiO thin films is controlled by electrical power and subject to Poisson distribution when electrical power consumed during switching is properly quantified [1]. The electrical power consumption values were quantified by grouping them with proper range, so that the data may be fitted to Poisson distribution with the normalized electrical power values of natural number m, as reported in [1].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical power consumption values were quantified by grouping them with proper range, so that the data may be fitted to Poisson distribution with the normalized electrical power values of natural number m, as reported in [1]. It was proposed in [1] that m may be equal to number of filaments either formed or ruptured during resistance switching based on the filamentary switching mechanism [1]. The number, however, has broad range and detailed study is required to understand how the quantified switching power values are related to filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the temperature distribution is another key factor governing the switching behavior. 10 Considering the different types of electrical carriers in TiO 2 ͑electron͒ and NiO ͑hole͒, local rupture and recovery can occur in a region near the cathode interface in a metal/NiO/metal. Under the given bias condition, O 2− ions move to the anode ͑or even to the atmosphere͒, which results in an oxygen-deficient TiO 2−x in TiO 2 and nickel-excess Ni 1+x O in NiO.…”
mentioning
confidence: 99%
“…Filament formation, accompanied by oxygen ion movement in most cases, is a very disordered process. [4][5][6] This results in the fluctuations of various switching parameters, such as the switching voltage and on and off currents. The other reason originated from the distortion of the stimulus signal for initiating RS.…”
mentioning
confidence: 99%